The ever-evolving world of microbes: the current state of microbial taxonomy, genome evolutionary dynamics, and the potential impact on the future of agricultural microbials risk assessment - Karberg, Katherine A. (Frontiers in Bioengineering and Biotechnology, 2025)
Risk assessment frameworks for plant agricultural biotechnology products have been in place for decades, focused on the evaluation of living biotechnology products created through genetic engineering. These products contain genetic material from outside the breeder’s gene pool, which is often from different taxa or represents “novel combinations of genetic material”. These products are typically considered to be “genetically modified” (GM) organisms in regulatory jurisdictions. However, in the microbial world, particularly among Bacteria and Archaea, the rapid expansion of genome sequence databases shows that natural microbial innovation primarily occurs through the natural exchange of genetic material from various sources, even from different taxa. This means that many microbes can be considered naturally occurring GM organisms. This raises the question of whether labeling a microbe as GM is always scientifically relevant for risk assessment. In most regulatory frameworks, being classified as GM significantly impacts the registration path, especially for microbes intended for environmental release. A more effective and science-based regulatory approach would assess the actual functions of a microbe rather than relying on the uncertain classification of its genetic material. This would benefit regulators, developers, and society by promoting the use of microbial technologies for agricultural use.